2019
DOI: 10.1177/0145561319878952
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Evoked Myogenic Potentials in Patients With Low Vitamin B12 Levels

Abstract: Objective:Vitamin B12 deficiency-induced hyperhomocysteinemia has been associated with impaired microarterial flow, demyelization, and neuronal damage, resulting in cochlear damage and auditory dysfunction. Therefore, we aimed to evaluate the possible vestibular-evoked myogenic potential (VEMP) abnormalities in patients with vitamin B12 deficiency.Material and Method:In this prospective study, 37 patients diagnosed with vitamin B12 deficiency (<220 pg/mL) were compared with 31 audiologically healthy partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The authors also reported some improvement in patients following B12 replacement, suggesting a relationship between B12 deficiency and auditory dysfunction. In another study, it was shown that increased rates of absent vestibular evoked myogenic potentials and decreased amplitudes with normal latencies in patients with vitamin B12 deficiency attributed to peripheral vestibular hypofunction 20 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors also reported some improvement in patients following B12 replacement, suggesting a relationship between B12 deficiency and auditory dysfunction. In another study, it was shown that increased rates of absent vestibular evoked myogenic potentials and decreased amplitudes with normal latencies in patients with vitamin B12 deficiency attributed to peripheral vestibular hypofunction 20 …”
Section: Discussionmentioning
confidence: 98%
“…In another study, it was shown that increased rates of absent vestibular evoked myogenic potentials and decreased amplitudes with normal latencies in patients with vitamin B12 deficiency attributed to peripheral vestibular hypofunction. 20 It was reported that B12 deficiency was associated with increased inflammation, and hearing loss is perhaps the result of inflammation. 21 As another mechanism, increased methylmalonic acid as a result of vitamin B12 deficiency can cause neurotoxicity and vasculotoxicity in the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…In other in vivo trials with mice fed an edible mushroom, Coriolus versicolor, revealed no change in the dentate gyrus volume or proliferation in newly generated neurons. It was found that mice treated with this mushroom biomass supplementation had a significant increase in the complexity of the long and short immature neurons (increase in dendritic complexity) (63).…”
Section: Targeting Neurogenisis With Mushroom Neutraceuticalsmentioning
confidence: 95%
“…Diet and dehydration can also cause blood pressure to drop, which can lead to dizzy spells. Prolonged episodes of whirling vertigo along with hearing problems in one ear, could be Ménière's, while frequent bouts about dizziness and vertigo can also indicate B12 deficiency [63].…”
Section: Mushroom Nutrition On Ménière's Diseasementioning
confidence: 99%
“…Diet and dehydration can also cause blood pressure to drop, which can lead to dizzy spells. Prolonged episodes of whirling vertigo along with hearing problems in one ear could be Ménière's, while frequent bouts of dizziness and vertigo can also indicate B12 deficiency [127].…”
Section: Mushroom Nutrition In Ménière's Diseasementioning
confidence: 99%